Application of a risk management system to improve drinking water safety - Asoka Jayaratne (2006)
The use of a comprehensive risk management framework is considered a very effective means of managing water quality risks. There are many risk-based systems available to water utilities such as ISO 9001 and Hazard Analysis and Critical Control Point (HACCP). In 2004, the World Health Organization’s Guidelines for Drinking Water Quality recommended the use of preventive risk management approaches to manage water quality risks. This paper describes the framework adopted by Yarra Valley Water for the development of its Drinking Water Quality Risk Management Plan incorporating HACCP and ISO 9001 systems and demonstrates benefits of Water Safety Plans such as HACCP.